CNC Programming Software Design to Optimizing Batik Stamping Time - Rian Prasetyo; Ainur Komariah (OPSI, 2021)
Batik is an original Indonesian heritage, that must be preserved and it is the mainstay for implementation of “Making Indonesia 4.0”. It was published many research about stamp batik manufacturing, but still have limitation of motive variation and slackly design process. This research aim to develop the way to making CNC program to be quickly, besides of high variation of batik motive. Source code in python programming language, was built for extension tool in inscape software. Extentension is used to create stamp point, depend on various motive size. Source code created in .py and .inx format will be save in “ekstensi” folder. Based on coordinate point of stamping in stamp batik, CNC program will be created, using “G-code tools” extension that was available in inscape software menubar. CNC programming used extension was built is measured about  time of process and compared to manual CNC programming. CNC program that has been built then tested in CAMotics software. The results of this research show that CNC program could maked with this extension for various dimension od batik stamp and in 2, 4, 6, 8, 10, and 12 meters of cloth length. CNC programming with extension developed, can reduce time up to 96.05%.